PERAN MANAJEMEN TALENTA DAN TUNJANGAN KINERJA DALAM MENINGKATKAN KINERJA KARYAWAN MELALUI KOMITMEN ORGANISASI - Afrida Salfadani; Sutrisno Sutrisno; Ika Indriasari (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research was conducted to determine the role of talent management and performance allowances in improving employee performance through organizational commitment at the Central Java Province Department of Industry and Trade. The research method uses quantitative research. The sample taken was 182 employees. Data analysis in this study used the Partial Least Square (PLS) method with calculations using Smart PLS 4.0 software. The research results concluded that talent management variables have a role in improving employee performance and organizational commitment, performance allowances play a role in increasing organizational commitment but do not play a role in improving employee performance, organizational commitment plays a role in improving employee performance.